Efficiency analysis of an improved biomass (charcoal) dryer constructed at the Center for Food Technology and Research, Benue State University, Nigeria - Gaydaybu, James Flomo; Achimba, Orseer; Udefi, Ifeyi; Nuredee, Mobolaji Rasheed; Obahi, Coolaid Aham; Tsenzughui, Geoffrey A; Ujah, Solomon (Journal of Postharvest Technology, 2024)
The dryer was evaluated by drying Nile Tilapia, Giraffe Catfish, and Mud Catfish all procured from the Wadata market, Makurdi Metropolis.  The data were analyzed using, Statistical Package for Social sciences (SPSS) version 25, Analysis of Variance (ANOVA) Post hoc Games  Howell and Fisher’s Least Significant Difference (F-LSD) tests and means were also separated at 95% confident interval. The Nile Tilapia  moisture content was reduced from 77.13% to 12.98% wb for six hours, the Giraffe Catfish moisture content was reduced from 79.31% to  13.26% wb for six hours while the Mud Catfish moisture was also reduced from 81.07% to 13.25% wb for eight hours using the Improved  Dryer. The charcoal was fed into the charcoal chamber as one Kg per hour with a maximum temperature of 130oC. The maximum drying rate  was 134 g/h recorded during the Giraffe Catfish drying and the dryer mean efficiency was 69.25%. The maximum relative humidity was  76%while also the maximum ambient temperature was 40oC. The data analyzed showed that there were no significant differences in the  temperature means per tray statistically. The sun-drying took 26 hours to reduce the moisture content of Nile Tilapia from 77.34% to 22.06%  wb, the Giraffe Catfish moisture content was reduced from 78.86% to 26. 08% wb while the Mud Catfish moisture content was also reducing  from 81.03% to 31.26% wb. The sun-drying couldn’t dry the samples to recommend safer moisture content for fish.
Keywords: Drying,; efficiency; biomass; fish and moisture